Deciphering Genetic Determinants of Behavioural Traits in Indigenous Cattle: A Review (Indian Journal of Animal Production and Management, 2024)
Exploring the realm of behavioral genetics  holds profound significance in research, given the  intricate and varied behavioral manifestations  displayed by domestic animals. These behaviors,  marked by both commonalities and distinctions  across species, wield considerable influence over  animal well-being and productivity. This  comprehensive review delves into the genetic  dimensions of behavior, elucidating the application  of behavioral genetics in breeding initiatives and its  pivotal role in unravelling the inherent genetic  diversity within these traits. In the context of cattle,  temperament traits are pivotal components of their  overall well-being, encompassing responses to  various activities such as handling, milking, and  challenges like human interactions during calving or  engagements with conspecifics. The genetic  foundations of these traits have been subjects of  rigorous study, with heritabilities estimated, and in  some cases, quantitative trait loci (QTL) pinpointed.  Despite the notable variability in these traits, certain  handling temperament traits exhibit moderate  heritabilities, rendering them amenable to selective  breeding. However, the integration of temperament  traits into selection programs remains somewhat  limited. Animals typically undergo screening for  behaviors like aggression or excessive fear during  handling or milking, resulting in the removal of  extreme cases. While estimated breeding values  (EBVs) for temperament are occasionally  determined, these traits are not consistently  incorporated into selection indices, despite their  potential economic, welfare, and human safety  implications. Challenges include the collection of  behavioral data on sufficiently large animal  populations for estimating genetic parameters and  the complexity of assigning economic values to  temperament traits. The discourse also considers  the implications of primarily selecting for  productivity traits on temperament and welfare.  Moving forward, opportunities lie in capitalizing on  automated data collection methods and more  extensive utilization of genomic information in the  selection process.
Keywords: animal welfare; dairy cattle; genetic parameters; genetic variation; milking temperament